SOME THOUGHTS (‮اﺗﺑﺎع اﻟﺳﻧﺔ‬): : ON THE MEANING OF "FOLLOWING THE SUNNAH" (Paper presented to the Third World Conference on the Sirah and the Sunnah—24—29th November, 1979 in Doha, Qatar) - Mackeen, Abḍul Majid (Islamic Studies, 1981)
N/A